Impact of microRNA dynamics on cancer hallmarks: An oral cancer scenario - VG Manasa; S Kannan (Tumor Biology)
MicroRNAs are endogenous small noncoding RNAs that negatively regulate gene expression at posttranscriptional level. The discovery of microRNAs has identified a new layer of gene regulation mechanisms, which play a pivotal role in development as well as in various cellular processes, such as proliferation, differentiation, cell growth, and cell death. Deregulated microRNA expression favors acquisition of cancer hallmark traits as well as transforms the tumor microenvironment, leading to tumor development and progression. Many recent studies have revealed altered expression of microRNAs in oral carcinoma with several microRNAs shown to have key biological role in tumorigenesis functioning either as tumor suppressors or as tumor promoters. MicroRNA expression levels correlate with clinicopathological variables and have a diagnostic and prognostic value in oral carcinoma. For these reasons, microRNA has been a hot topic in oral cancer research for the last few years. In this review, we attempt to summarize the present understanding of microRNA deregulation in oral carcinoma, their role in acquiring cancer hallmarks, and their potential diagnostic and prognostic value for oral cancer management.